PENERAPAN NEKAY (BONEKA KULIT KAYU) SEBAGAI KONSEP EDUECOTOURISM UNTUK MENDUKUNG PROGRAM DESA RAMAH PEREMPUAN DAN PERLINDUNGAN ANAK DI KAMPUNG ASEI KABUPATEN JAYAPURA - Suseno, Bayu Aji; Utami, Putri Prabu; Astuti, Retnoning Adji Widi; Murda, Muhammad Ilham Mustain; Rinantanti, Yulini; Wafom, Yunus; Koyari, Yanes (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2026)
The development of Asei Village as a pilot village for the Women's Friendly and Child Protection Village (DRPPA) program has not yet been accompanied by activities that support play and learning spaces for children, as well as women's economic empowerment to enhance artistic entrepreneurship based on the potential of local materials (Khombouw bark). This community service activity aims to provide training in creating bark puppet theater performance models (NEKAY) for women (mama-mama) bark artisans in Asei Village. The Asset-Based Community Development (ABCD) method is used in this community service activity through four stages: (1) socialization of environmental- and education-based sustainable tourism (educotourism) programs; (2) training in sketching, creating basic patterns, assembly techniques, doll finishing, and the production of NEKAY ASEI performance merchandise in the form of gift-set hamper souvenirs; (3) assistance in developing performance models through training in vocal performance, musical accompaniment for NEKAY theater performances, and puppet manipulation techniques (movement), using monologue drama scripts based on the stories Friends of Animals and Mama Asei; and (4) development of the NEKAY ASEI theatrical performance through marketing strategies covering the production process, promotional media, and preparation for public performances. The output targets of this community service activity are performance props in the form of Khombouw bark puppets depicting indigenous Papuan children and endemic Papuan animals (the Bird-of-Paradise and the Waigeo Cuscus), as well as the addition of one female character (Mama Asei), and three children's songs with more cheerful and energetic musical arrangements that convey themes of friendship between humans and animals, as well as parental love for children. Pengembangan Kampung Asei sebagai desa percontohan program Desa Ramah Perempuan dan Perlindungan Anak (DRPPA) masih belum disertai dengan kegiatan yang menunjang ruang bermain dan belajar bagi anak, serta pemberdayaan ekonomi perempuan untuk meningkatkan kewirausahaan seni berbasis potensi material lokal (kulit kayu Khombouw). Kegiatan pengabdian ini bertujuan untuk memberikan pelatihan pembuatan model pertunjukan teatrikal boneka kulit kayu (NEKAY) bagi perempuan (mama-mama) pengrajin kulit kayu di Kampung Asei. Metode Asset Based Community Development (ABCD) digunakan dalam kegiatan pengabdian melalui empat tahapan, antara lain: (1) sosialisasi program pariwisata berkelanjutan berbasis lingkungan dan edukasi (eduecotourism); (2) pelatihan pembuatan sketsa, pola dasar, teknik perakitan, finishing boneka & pelatihan pembuatan produk merchandise pertunjukan NEKAY ASEI dengan format gift set hampers souvenir, (3) pendampingan model pertunjukan dengan pelatihan olah vokal dan musik iringan pertunjukan teater NEKAY dan teknik manipulasi (gerak) boneka dengan naskah drama monolog cerita Sahabat Satwa dan Mama Asei, (4) pengembangan pentas seni teatrikal NEKAY ASEI dengan menggunakan strategi pemasaran mulai dari proses pembuatan, media promosi hingga siap untuk dinikmati oleh penonton. Target luaran dari kegiatan pengabdian ini adalah alat peraga pertunjukan berupa boneka kulit kayu yang berbentuk anak asli Papua dan binatang satwa endemik Papua (Burung Cenderawasih dan Kuskus Waigeo), serta tambahan satu buah karakter tokoh perempuan (Mama Asei), serta tiga buah lagu anak-anak dengan aransemen musik yang lebih ceria dan energik yang bertemakan tentang persahabatan antara manusia dengan hewan, serta kasih sayang orang tua terhadap anak.